Evaluation of functions and values of Attica wetlands in Greece - Σ. Κατσαβούνη; Μ. Σεφερλής (Greek Biotope/Wetland Centre (EKBY), 2017)
The document is a synopsis of the Greek version and comprises the following chapters: Study areas: Brief description of the study areas: 1) Asopos estuary and Oropos lagoons, 2) Marathonas reservoir, 3) Sxinias national park, 4) Loutsa wetland, 5) Vravrona wetland, 6) Lake Vouliagmeni, 7) Lake Koumoundourou, 8) Vourkari wetland, and 9) Psatha wetland. Functional evaluation methodological approach: The WET method for the assessment of wetland functions and values and the HydroGeoMorphological approach (HGM) applied in two wetland sites, are presented. Assessment of wetland functions and values: The results of the functional assessment of Attiki’s wetlands are summarized in tables.